Water Activated by a Microwave Plasma Argon Jet as a Factor Stimulating the Germination of Plant Seeds - Sergeichev, K. F.; Lukina, N. A.; Apasheva, L. M.; Ovcharenko, E. N.; Lobanov, A. V. (Russian journal of physical chemistry. B, 2022)
Using the new electrodeless microwave technology for generating plasma in an open atmosphere, solutions of hydrogen peroxide and nitrogen compounds are obtained from distilled water. The method is based on the activation of distilled water by a jet of thermal argon plasma of an electrodeless microwave discharge in air at atmospheric pressure. Plasma-activated water has a stimulating effect on seed germination and plant growth, which is much more effective than the effect of industrial hydrogen peroxide solutions with stabilizing additives.